Hyperchaotic Circuit Based on Memristor Feedback with Multistability and Symmetries - Xiaoyuan Wang; Xiaotao Min; Pengfei Zhou; Dongsheng Yu (Complexity)
A novel hyperchaotic circuit is proposed by introducing a memristor feedback in a simple Lorenz-like chaotic system. Dynamic analysis shows that it has infinite equilibrium points and multistability. Additionally, the symmetrical coexistent attractors are investigated. Further, the hyperchaotic system is implemented by analogue circuits. Corresponding experimental results are completely consistent with the theoretical analysis.